Quantitative oxidation of nutrients in broiler treated with b-agonist l-644,969 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Effects of 13-agonist L-644,969 on nutrient oxidation were evaluated in broiler chickens allocated into twelve cages with six chicken per cage during the first week and three chickens in the following five weeks of the experiment. The 13-agonist L-644,969 was given at the doses of 0 (TO), 0.25 (T1) and 1.0 (T2) ppm. The contribution of each nutrient to the total heat production showed that L-644,969 decreased the protein oxidation and increased fat oxidation. Lipogenesis from carbohydrate made up the main contribution (69 to 74%) to the total fat retention. In contrast, fat retention from protein (6 to 8%) was the minor contribution, and there was no difference between control and treatment groups. The conversion of dietary fat to fat stored directly in the body ranged from 24% in the control to 8% at 1.0 ppm level. This study supports previous findings that the B-agonist L-644,969 increased protein utilization and decreased fat deposition.